Here's the question you clicked on:
Wiskomen
Hi everyone, since two days I'm following the lesson 18.01SC and I don't really understand this: In Session 2, Clip 2 he explaines that to get the x-intercept of the triangle you have to use this formula: y - y0 = m (x - x0) with: y = 0, because it is an intercept with the x-axes. y0 = 1/x0 m = -1/x0^2 x = x x0 = x0 But I don't get why it is y - y0 and not just y0 and why it is m (x - x0)... Could someone please help me with this? If it is a bit of a stupid question, I'm sorry.
Hi, thanks for you question, I think I understand it now... If I find an other problem that I can't figure out, I'll be back here. Thanks you so much!